Simulation Research of Potential Contrast Agents for X-Ray Fluorescence CT with Photon Counting Detectors - Yan, Luo; Peng, Feng; Ruge, Zhao; Yi, Zhang; Kang, An; Peng, He; Shenghao, Yan; Xiansheng, Zhao (Frontiers in Physics, 2021)
XFCT is a novel method for early cancer detection. Increasing concentration of contrast agents and incident X-rays’ energy were used to improve detecting accuracy, which greatly increased the prevalence of Contrast-induced nephropathy. Therefore, this research explores the adaptive contrast agents and uses Geant4 to simulate the imaging conditions of Pt, Bi, Gd, Ru, and Au for searching the lowest detectable concentration based on the proposed fast multi-pinhole collimated XFCT (fmpc-XFCT)imaging system and low incident energy. Several imaging parameters including pinhole radius(0.7mm, 0.8mm and 1mm) were adjusted, the optimized EM-TV algorithm were used to reconstruct XFCT images. It is found that Bi element is superior to other metal elements in terms of Contrast to Noise Ratio(CNR) and fluorescence efficiency, the lowest concentration can be detected is 0.12% with optimal parameters.